Analisis Polimorfisme Genetik sebagai Prediktor Respons Imun dan Efektivitas Terapi Standar pada Pasien Diabetes Melitus Tipe 2 - Novycha Auliafendri; Alex Handani Sinaga (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease with high prevalence and significant public health impact. This study aimed to analyze the association of IL-6 gene polymorphism (−174G>C) with serum IL-6 levels and the effectiveness of standard therapy assessed through HbA1c and Random Blood Glucose (RBG) in T2DM patients. A cross-sectional design was employed, involving 40 patients at Imelda Hospital. The polymorphism was examined using Polymerase Chain Reaction (PCR), serum IL-6 levels were measured with Enzyme-Linked Immunosorbent Assay (ELISA), while HbA1c and RBG were determined through standard laboratory analysis. The results indicated that IL-6 genotypes (GG, GC, CC) were not significantly associated with serum IL-6 levels, HbA1c, or RBG. In contrast, type of therapy showed a significant relationship with HbA1c, where patients receiving combination therapy achieved better glycemic control compared to those on monotherapy. These findings highlight that therapeutic regimen remains the primary determinant of glycemic control, whereas the role of IL-6 polymorphism in this study population appears limited. Further studies with larger sample sizes and broader genetic analyses are required to strengthen the application of precision medicine for diabetes management in Indonesia.